2006
DOI: 10.3892/or.15.1.149
|View full text |Cite
|
Sign up to set email alerts
|

p53 enhances the Δ-24 conditionally replicative adenovirus anti-glioma effect

Abstract: Abstract. Previous studies have demonstrated that the conditionally replicative adenovirus Ad5¢24 is a powerful cytolytic agent against glioma selectively affecting cells with a defective p16/Rb/E2F pathway. The p53 protein is also known to be an apoptotic factor for glioma cells. In this study, we examined the simultaneous delivery of the combination of exogenous p53 and Ad5¢24 adenovirus in glioma cells. Infecting cells with low doses of adenovirus p53 and Ad5¢24 resulted in an additive effect on cell death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In human brain tumor cells (glioblastoma, medulloblastoma) the E2F-1 promoter and in human melanoma cells the tyrosinase enhancer/promoter (hTyrE/P) drive the replication of the Ad-Delta24 viruses [415]. Ad5CMV--p53 and Ad5Delta24 doubly infected glioma cells were killed more efficiently than with either one of the viruses applied singly [255]. In killing glioblastoma cells, the topoisomerase antagonist irinotecan (CPT-11), or temozolomide, and an Ad-Delta24 derivative acted additively/synergistically [127].…”
Section: Adenovirusesmentioning
confidence: 99%
“…In human brain tumor cells (glioblastoma, medulloblastoma) the E2F-1 promoter and in human melanoma cells the tyrosinase enhancer/promoter (hTyrE/P) drive the replication of the Ad-Delta24 viruses [415]. Ad5CMV--p53 and Ad5Delta24 doubly infected glioma cells were killed more efficiently than with either one of the viruses applied singly [255]. In killing glioblastoma cells, the topoisomerase antagonist irinotecan (CPT-11), or temozolomide, and an Ad-Delta24 derivative acted additively/synergistically [127].…”
Section: Adenovirusesmentioning
confidence: 99%
“…Replacement of the p53 tumor suppressor gene is another rational approach to the management of malignant gliomas, since it is frequently mutated or inactivated in this cancer (Ito et al 2005;Nashimoto et al 2005;Gil-Perotin et al 2006;Mitlianga et al 2006;Senatus et al 2006). However, the transfer of exogenous wild-type p53 cDNA could cause apoptosis in glioma cells expressing endogenous mutant p53, but not in cells expressing endogenous wild-type p53 (Gomez-Manzano et al 1997).…”
Section: Adenovirus-based Vectors For Experimental Brain Tumor Therapymentioning
confidence: 99%
“…However, the transfer of exogenous wild-type p53 cDNA could cause apoptosis in glioma cells expressing endogenous mutant p53, but not in cells expressing endogenous wild-type p53 (Gomez-Manzano et al 1997). In vitro experiments showed that the combination of a replication-incompetent adenoviral vector serotype 5 (Adv5) carrying the apoptosis-inducing p53 gene and a cytolytic Adv (Adv5D24) specific to cells with a defective p16/Rb/ E2F pathway could enhance the oncolytic effect on gliomas (Mitlianga et al 2006). Recently, p53 upregulated modulator of apoptosis (PUMA) was identified as a p53-inducible pro-apoptotic molecule.…”
Section: Adenovirus-based Vectors For Experimental Brain Tumor Therapymentioning
confidence: 99%
“…These results indicated that Ad5CMV-p53 enhanced the oncolytic effect of the Delta-24 adenovirus. 43 E1 transcomplementation of a replication-competent adenovirus-encoding p53 resulted in dramatic augmentation of cell killing and circumvented resistance to apoptosis obviating the potential utility of therapeutic transgene expression by a replicating adenovirus. 44 Evaluation of AdDelta24-p53 in comparison with its parent Delta-24, showed better efficiency and caused more frequent regression of glioma xenografts.…”
Section: Oncolytic Viruses As Gene Carriersmentioning
confidence: 99%